Pelaksanaan Pembelajaran PJOK Materi Beladiri di SMP Kecamatan Watumalang Kabupaten Wonosobo Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
The introduction in this research is the implementation of PJOK learning in martial arts in SMP Watumalang District, Watumalang. The problem limitation in this research is planning, implementing, and evaluating. This study aims to determine how teachers carry out physical education, sports, and health learning in self-defense materials in schools. This study used descriptive qualitative method. The research instrument is the researcher himself. Data collection techniques, namely interviews, observation, and documentation. Data analysis techniques using data reduction, data display, and drawing conclusions. The researcher conducted research on 10 junior high schools in Watumalang Subdistrict, Wonosobo District, there were 8 schools that implement physical education martial arts learning and 2 schools that did not implement physical education martial arts learning. Schools that implement martial arts learning at Watumalang Subdistrict, Wonosobo District, see the learning process by planning learning, implementing learning, evaluating learning. Schools that did not implement physical education martial arts learning have various reasons that did not support the implementation of physical education martial arts learning, such as teachers who are not confident in their abilities due to different teacher competencies, moreover, in terms of unsupportive facilities and infrastructure also sports equipment that are not provided by schools, thus teachers are less interested in providing martial arts learning in schools. The conclusion is that in physical education martial arts learning at Junior High Schools in Watumalang Subdistrict, Wonosobo District in 2020 at 8 schools that implement martial arts learning in terms of planning, implementation and evaluation already good, only 3 out of 8 schools do not meet the implementation standards sub indicators. The 2 schools that did not implement physical education martial arts learning have many obstacles due to the potential of the teachers themselves and less supportive infrastructure. For suggestions, teachers should develop learning model that are more creative and innovative in learning, furthermore, teachers should develop their knowledge and potential in the field of martial arts so that teachers can provide martial arts learning. The education office is expected to provide upgrading and training for junior high school physical education teachers in Watumalang Subdistrict Wonosobo Disctrict through the MGMP in the martial arts subdivision.